Advancing gender-inclusive business models for cattle artificial insemination in Son La, Vietnam - Pazos Cardenas, Mateo; Bravo, Aura Maria; Triana Ángel, Natalia; Burkart, Stefan; Nguyen, Thinh; Le, Thi Thanh Huyen; Atieno, Mary; Phuong, Nguyen Thi Minh; Marshall, Karen (2025)
Artificial insemination (AI) is a transformative technology in cattle production, offering increased productivity and genetic improvement. However, in Son La province, Vietnam, its adoption remains limited, especially among women, despite their vital role in livestock care and management. This policy brief analyzes the gender dimensions of AI service provision in Son La, drawing on extensive field research including key informant interviews (KIIs) and focus group discussions (FGDs) with AI service providers, farmers, and stakeholders. It highlights key barriers, identifies enabling factors, and offers actionable recommendations for developing gender-sensitive and scalable AI business models. While men dominate technical and financial decision-making, women as farmers contribute significantly to daily animal care and herd health. In addition, as veterinary providers, women are limited in AI training and service delivery due to common cultural perceptions, physical misconceptions, and structural constraints such as mobility limitations, language barriers, and time poverty caused by domestic responsibilities. Nonetheless, the presence of successful women AI technicians in the province signals a transformative potential. With thoughtful intervention, AI services can be restructured to enhance gender equity, improve household livelihoods, and foster sustainable livestock development.